Membrane lipids in Agrobacterium tumefaciens: biosynthetic pathways and importance for pathogenesis - Aktas, Meriyem; Danne, Linna; Möller, Philip; Narberhaus, Franz (Frontiers in Plant Science, 2014)
Many cellular processes critically depend on the membrane composition. In this review, we focus on the biosynthesis and physiological roles of membrane lipids in the plant pathogen Agrobacterium tumefaciens. The major components of A. tumefaciens membranes are the phospholipids (PLs) phosphatidylethanolamine (PE), phosphatidylglycerol (PG), phosphatidylcholine (PC) and cardiolipin, and ornithine lipids (OLs). Under phosphate-limited conditions, the membrane composition shifts to phosphate-free lipids like glycolipids, OLs and a betaine lipid. Remarkably, PC and OLs have opposing effects on virulence of A. tumefaciens. OL-lacking A. tumefaciens mutants form tumors on the host plant earlier than the wild type suggesting a reduced host defence response in the absence of OLs. In contrast, A. tumefaciens is compromised in tumor formation in the absence of PC. In general, PC is a rare component of bacterial membranes but amount to ~22 % of all PLs in A. tumefaciens. PC biosynthesis occurs via two pathways. The phospholipid N-methyltransferase PmtA methylates PE via the intermediates monomethyl-PE and dimethyl-PE to PC. In the second pathway, the membrane-integral enzyme PC synthase (Pcs) condenses choline with CDP-diacylglycerol to PC. Apart from the virulence defect, PC-deficient A. tumefaciens pmtA and pcs double mutants show reduced motility, enhanced biofilm formation and increased sensitivity towards detergent and thermal stress. In summary, there is cumulative evidence that the membrane lipid composition of A. tumefaciens is critical for agrobacterial physiology and tumor formation.